Tryck ett för generositet, tryck två för skam - Sedström,Daniella; Lindqvist,Lisa (2026)
This study aims to deepen the understanding of how automated tipping systems affect guests' restaurant experiences and service interactions in the context of limited bar service in Sweden. Specifically, the study examines how social norms and moral perceptions shape tipping behaviour, what level of service is considered sufficient to warrant a tip and how the design of automated tipping requests influences the guests value creation process. The study uses a qualitative and abductive research approach. Data was collected through seven semi-structured interviews with guests and bartenders, as well as two participant observations at pubs in Helsingborg and Malmö. The interviewees were between 19 and 56 years old, consisting of three men and four women, with three bartenders and four guests. The analysis was guided by an analytical model combining Azar’s (2004) theory of social norms, moral economy, equity theory and value co-creation and value co-destruction. The findings show that tipping in Sweden is a situationally bound social norm. Tipping requests are considered legitimate at sit-down dinner service but much less legitimate at simple bar service. Few examples of social sanctions for not tipping were observed. Moreover, the Swedish collective agreement and fixed wages may function as a moral relief for guests, since staff have a secure base salary. However, feelings of shame and guilt can arise when guests actively have to decline tipping options, partly due to internalized norms active in other contexts. This in turn was partly due to the design of the card terminal, which several informants described as psychologically pressuring. Automated tipping systems can therefore challenge culturally and socially embedded notions of when tipping is actually justified. When technical changes disrupt established norms, negative reactions may arise. The primary recommendation is that establishments with limited service should consider whether to offer tipping options at all. If tipping options are retained, they should be designed more discreetly to better reflect voluntariness. Finally, the study should be read as an investigation of perceptions and beliefs about tipping, rather than tipping behaviour as such.
Keywords: Social norms; moraleconomy; value co-creation; value co-destruction; equity theory; tipping behaviour; automated systems; limited service